Barron's E-Z grammar - Mulvey, Dan. (Hauppauge, N.Y. : Barron's Educational Series, 2009)
Reviews basic grammar, including parts of speech, sentence structure, and subject-verb agreement; provides a manual of usage, instruction on writing paragraphs and research papers, and how to develop one's own style; and includes exercises and a test.
Includes index.
Originally published: 1st ed. Grammar the easy way, 2002.
Keywords: English language -- Grammar